ChemInform Abstract: Synthesis of γ‐Lactams and γ‐Lactones via Intramolecular Pd‐Catalyzed Allylic Alkylations. Issue 15 (April 2015) - Kammerer, Claire; Prestat, Guillaume; Madec, David; Poli, Giovanni
Abstract: Review: 37 refs.